BIOSORPTION OF PHENOL BY A CHEMICALLY TREATED WILD MACROFUNGUS: EQUILIBRIUM AND KINETIC STUDY - R. VIMALA; A. NIRMALA GRACE (International Journal of Pharma and Bio Sciences, 2013)
Phenol is one of the most common water pollutants found in industrial effluents. The phenol removal potential of a chemically modified macrofungus Trametes sp., was investigated in a batch system. The effects of particle size, pH, temperature, contact time and biosorbent dosage have been investigated. The optimum conditions for phenol removal were found to be particle size: 150-300 µm, pH: 6.0 and biosorbent dosage: 6 g/L. The rate of biosorption of phenol was found to be rapid during the initial 30 min and equilibrium was established after 4 h. The results of equilibrium isotherm study showed that the data fitted well to Langmuir isotherm model within the concentration range studied (100-500 mg/L). The maximum adsorption capacity of the biosorbent was found to be 39.37 mg/g. Sorption kinetics was well described by pseudo-second-order kinetics. Desorption with 0.1 M NaOH resulted in 87% desorption of phenol from the biosorbent. The present study proved the applicability of Trametes sp., for the removal of phenol from waste waters.